2020
DOI: 10.1016/j.neuron.2020.03.008
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster of Autism-Associated Variants on X-Linked NLGN4X Functionally Resemble NLGN4Y

Abstract: Highlights d Despite sharing 97% amino acid identity, NLGN4X and NLGN4Y are differentially regulated d NLGN4Y cannot traffic to the surface due to one amino difference from NLGN4X d A cluster of autism-associated variants in NLGN4X surrounds the critical amino acid d NLGN4X autism-associated variants display a deficit in trafficking similar to NLGN4Y

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…Given that there is a homologous gene on the Y chromosome, NLGN4Y , X inactivation escape may be important for dosage compensation between males and females. However, new evidence suggests that NLGN4Y is processed differently than NLGN4X and is not trafficked to the cell surface and does not contribute to the formation of synapses (Nguyen et al, 2020). Thus, any decrease in NLGN4X expression may be deleterious.…”
Section: Discussionmentioning
confidence: 99%
“…Given that there is a homologous gene on the Y chromosome, NLGN4Y , X inactivation escape may be important for dosage compensation between males and females. However, new evidence suggests that NLGN4Y is processed differently than NLGN4X and is not trafficked to the cell surface and does not contribute to the formation of synapses (Nguyen et al, 2020). Thus, any decrease in NLGN4X expression may be deleterious.…”
Section: Discussionmentioning
confidence: 99%
“…What is the function of NLGN4Y if it cannot get to the surface? Nguyen et al (2020) demonstrated that NLGN4Y can oligomerize with NLGN1, 2, 3, and 4X and reduce their surface trafficking. In addition, exogenously expressed NLGN4Y on a WT background decreased mEPSCs suggesting NLGN4Y acts to inhibit NLGN1-3 function.…”
Section: Nlgn4x and Nlgn4ymentioning
confidence: 99%
“…To explore the function of NLGN4Y, in a recent study, we directly compared NLGN4X and NLGN4Y and found that NLGN4Y cannot traffic to the surface to induce synapses (Nguyen et al, 2020). Furthermore, the differential trafficking observed between NLGN4X and NLGN4Y is due to an amino acid difference at position 93, with proline for NLGN4X and serine for NLGN4Y.…”
Section: Nlgn4x and Nlgn4ymentioning
confidence: 99%
See 2 more Smart Citations